Assessment of enrichment planting of teak (Tectona grandis) in degraded dry deciduous dipterocarp forest in the Central Highlands, Vietnam. Issue 1 (2nd January 2018) - Huy, Bao; Tri, Pham Cong; Triet, Tran
Abstract : After years of unsustainable logging, dry deciduous dipterocarp forest (DDDF) has become poor in timber stocks and has been converted to industrial crops such as rubber. The objectives of this study were to assess teak ( Tectona grandis L.f.) tree establishment under degraded DDDF conditions and to determine factors that influence the suitability of teak as a forest enrichment tree species. A set of 64 experimental plots of 4 900 m 2 each was set up and observed for 4–5 years for testing enrichment planting with teak under various combinations of two groups of factors: ecological conditions and forest status. Weighted, non-linear, multivariate regression models were used to detect key factors that influenced the suitability of teak. The results showed that at the age of 4 years the average dominant tree height (defined as 20% of the tallest trees in the experimental plot) reached 11.2, 7.8, 5.3 and 3.8 m for very good, good, average and poor suitability levels, respectively. Survival rates of planted teak from average to very good suitability levels were over 90%. Six key factors that affected the suitability of teak were waterlogging during the rainy season, altitude, stand volume of the degraded DDDF, soil type, percentage of sand and concentration of P2 O5 in the soil. Under the extreme ecological and environmental conditions of the DDDF, enrichment planting with teak gave promising results.